Egypt's Nile water policy under Sisi: Security interests promote rapprochement with Ethiopia - Tobias von Lossow; Stephan Roll (Stiftung Wissenschaft und Politik (SWP), 2015)
Under Abdel Fatah al-Sisi Egypt has moderated its stance in the Nile water dispute with Ethiopia, the most important state upstream. In the conflict over the Grand Ethiopian Renaissance Dam (GERD), Cairo is now seeking cooperation rather than conflict. But this rapprochement is not driven by any fundamental reversal in Egypt's Nile water policy. Instead, Cairo recognises that its options are restricted by the advanced state of dam construction. In addition it sees Ethiopia as an increasingly important partner, especially in matters of regional security. While Egyptian-Ethiopian conflict over distribution and usage of the water is currently on the back-burner, the issue is by no means resolved. (SWP Comments)
Keywords: 320